1991
DOI: 10.3109/10428199109070277
|View full text |Cite
|
Sign up to set email alerts
|

A 20 Year Clinical and Laboratory Study of Familial B-Chronic Lymphocytic Leukemia in a Single Kindred

Abstract: Four siblings and a parent in a single kindred had documented blood and marrow lymphocytosis during the past 18 to 20 years consistent with chronic lymphocytic leukemia (CLL). Of the four siblings, one developed a spontaneous remission; one died secondary to subepiglotitis with sepsis; one died with prolymphocytoid transformation and one remains alive with splenomegalic CLL. Lymphadenopathy and splenomegaly were variable as was the clinical response to chemotherapy. Bone marrow morphology was initially nodular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Epidemiological studies have shown that the risk of CLL in relatives of patients with CLL is increased and it is likely that a subset of the disease is caused by a genetic susceptibility (Fraumeni et al, 1969;Neuland et al, 1983;Blattner et al, 1987;Caporaso et al, 1991Caporaso et al, , 1997Goldin et al, 1999;Yuille et al, 2000;Ishibe et al, 2001Ishibe et al, , 2002a. As CD5 + 23 + MBL may be a precursor of CLL, it has been postulated that MBL might be overrepresented in apparently healthy relatives of familial CLL cases.…”
Section: Populations To Considermentioning
confidence: 99%
“…Epidemiological studies have shown that the risk of CLL in relatives of patients with CLL is increased and it is likely that a subset of the disease is caused by a genetic susceptibility (Fraumeni et al, 1969;Neuland et al, 1983;Blattner et al, 1987;Caporaso et al, 1991Caporaso et al, , 1997Goldin et al, 1999;Yuille et al, 2000;Ishibe et al, 2001Ishibe et al, , 2002a. As CD5 + 23 + MBL may be a precursor of CLL, it has been postulated that MBL might be overrepresented in apparently healthy relatives of familial CLL cases.…”
Section: Populations To Considermentioning
confidence: 99%
“…CLL is the most common adult leukemia and familial CLL exhibits the most frequent familial aggregation among hematological malignancies (1–3). Familial and sporadic chronic lymphocytic leukemia have been extensively studied and the clinical presentation, molecular and cytogenetic properties compared (7, 14). Clinical anticipation (earlier age of onset and/or increased severity in successive generations) is well characterized in familial CLL (6, 8).…”
Section: Discussionmentioning
confidence: 99%
“…Familial aggregation of chronic lymphocytic leukemia (familial CLL) has been observed more frequently than familial aggregation in any other hematological malignancies. Familial CLL families provide the unique opportunity to identify susceptibility genes and other factors that contribute in the etiology of CLL (3–10). Familial CLL and sporadic CLL have been studied with regard to their clinical presentation, anticipation, genetics, and molecular abnormalities; however, no study has been conducted to evaluate and compare patterns of cell surface antigen expression.…”
mentioning
confidence: 99%
“…B‐cell CLL exhibits a high degree of familial clustering (Gunz et al , 1975; Caporaso et al , 1991; Ishibe et al , 2001), and for over 25 years, the National Cancer Institute (NCI) of the National Institutes of Health (NIH, Bethesda, MD, USA) has studied kindreds with two or more affected family members. Members of the kindreds are invited to visit the NIH Clinical Center and participate in studies that seek to identify genetic and environmental factors that contribute to disease in their families.…”
Section: Methodsmentioning
confidence: 99%